Applying the affective events theory to explore the effect of daily micro-interruptions on mental health: the mediating role of affect and the moderating role of pets at work - Junça Silva, A. (The Spanish Journal of Psychology, 2024)
This study relied on the affective events theory and the social exchange theory to develop a framework that explains how situational factors (daily micro-interruptions) enhance affective reactions (negative affect) and, in turn, impair health conditions (mental health) at work. We further delineate theoretical arguments to propose the pet-human’s health effect by demonstrating that pets are boundary conditions that attenuate this relation, and as such are protective conditions for employees’ mental health. We conducted a 5-day diary study with two groups of participants, one with participants who owned pets (N = 82 x 5 = 410), and the other who did not own pets (N = 87 x 5 = 435). The multilevel results showed an indirect effect of daily micro-interruptions on individuals’ mental health through negative affect, with a daily backdrop of poorer mental health for those who did not own a pet (compared to those who owned a pet). These results evidence the benefits of owning a pet for individuals’ mental health, even at work, and as such provide recommendations for teleworking practices. Moreover, this study resorts to an innovative and robust data collection method to demonstrate the pet-human’ health effect. This study expands knowledge on the role of pets in working daily routines and shows that pets may be a personal resource for individuals while working.